ChemInform Abstract: Palladium‐Catalyzed Vinylselenation of Allenes. Issue 20 (25th April 2013) - Fujiwara, Shin‐ichi; Okuyama, Maiko; Tsuda, Susumu; Iwasaki, Takanori; Kuniyasu, Hitoshi; Kambe, Nobuaki
Abstract Pd‐cataylzed treatment of allenes with activated vinyl selenides is found to result in efficient and regioselective formation of 2‐selenomethyl‐1, 3‐dienes.